Technology and Media Use in Preschool Classrooms: Prevalence, Purposes, and Contexts - Dore, Rebecca A.; Dynia, Jaclyn M. (Frontiers in Education, 2020)
Although the amount of time that preschoolers spend with screen media at home is continuing to increase, less is known about the types of media experiences children are having in preschool settings. Furthermore, little research has investigated the purposes for which preschool teachers use technology and media in the classroom and the contexts in which such use occurs. The current study addresses that gap by providing a nuanced picture of technology and media use in preschool classrooms. Lead teachers were recruited via email lists of educators who participated in previous studies or expressed interest in receiving communication from our research group. Participants (N = 312, 98.6% female; Mage = 43.9 years) all taught preschool-age children. Participants were first asked to check which of four devices they used with children in their classroom (tablet, smartphone, computer, television). If participants responded that they used each device, they were asked how often. Survey items also assessed (1) Purposes: how often teachers used each device for instructional purposes (e.g., teaching new material, practicing material) and non-instructional purposes (e.g., entertainment, as a reward), and (2) Context: how often teachers used devices for both teacher-supported and non-teacher-supported activities. Results indicated that tablet and computer use were most common, whereas smartphone and television use were less prevalent. Teachers reported most frequently using tablets, computers, and smartphones for instructional purposes. Television was most frequently used for entertainment. Tablets and smartphones were most frequently used in teacher-supported individual contexts, whereas computers were most frequently used in teacher-supported whole group contexts. Latent class analysis showed five classes of classroom technology and media use: tablet and computer users, tablet only users, low technology users, computer for teacher-supported instruction users, and television only users. Finally, we determined that these classes were predicted by program funding (publicly- or privately-funded), teacher experience, and teacher education.